DESIGNING READING MATERIAL BASED ON BATAKNESE FOLKLORE - Elen Sitompul; Hotmauli Situmorang; Rika Sipayung; Uni Siburian (English Language Teaching Prima Journal (ELT), 2021)
Abstract The low level of reading comprehension and interest affects their learning motivation at school. Many students are not interested in reading, because they think it is boring. To overcome these problems, this research aims: first, to develop Batak folklore. Second, to determine the effect of Batak folklore on reading comprehension and student motivation. This study takes 3 Batak folklore including 1) The Legend of Pohon Aren, 2) The Legend of Aek Situmandi, 4) The Legend of Air Soda. This type of research is a qualitative descriptive obtained in writing to describe the moral values and character formation contained in the 3 Batak folk tales. The data of this research were taken from students of SMK Telkom Medan. Data collection is done by reading the story text over and over again. From the research, it can be concluded that Batak folklore can increase students' interest in reading and can be a motivation for every student. Keywords: Batak folklore, motivation, reading interesting